Breastfeeding and social, cultural, geopolitical embodied barriers - Castaldo, Miriam; Marrone, Rosalia (Ra Ximhai, 2024)
This study in medical anthropology was conducted at the National Institute for Health, Migration and Poverty (INMP), in Rome, Italy, and was carried out in 2013-2014 as part of the project “Clinical and social evaluation of medical practices in the treatment of infectious diseases in paediatrics for children of vulnerable populations”. At the end of the project, it was possible to ensure diagnostic accuracy, the proper prescription of antibiotic therapy and improve family care of children affected by <a href="https://posta.inmp.it/owa/redir.aspx?C=3NtbIJUNa0m0Lvo9kHPezV-2R7RZk9MIySbhdDQzL0LUGoIMRCroM_qYAFbycla4PsYagW4oTo4.&URL=https%3a%2f%2fwww.google.it%2fsearch%3fbiw%3d1440%26bih%3d782%26q%3dpharyngotonsillitis%26spell%3d1%26sa%3dX%26ved%3d0ahUKEwjTkuGU6ovNAhXD1xQKHSXaBcUQvwUIGSgA">pharyngotonsillitis. In addition, it was possible to acquire knowledge of the health of children with respect for certain social determinants. The anthropological research targeted mother’s of children and adolescents from the age of 3 to the age of 17 immigrated to Rome from Africa: sub-Saharan and North; furthermore from Asia: Indian subcontinent, West Asia, Eurasia, Middle East, Arabian peninsula; South-East Europe; Centre and South America. In this article we’ll consider only mother’s of 39 children and adolescents from Latin America (Argentina, Brazil, Colombia, Ecuador, El Salvador, Honduras, Nicaragua, Paraguay, Peru, Dominican Republic, Uruguay and Venezuela). The study aimed at analysing the formation and the socio-cultural representation, which emerged from interviews of women regarding barriers to breastfeeding; the effects of breastfeeding on the psychological and physical health of infants; the social and domestic consequences, which affect women who did not stop breastfeeding when they feel they should have. In Italy, as in other destination countries for global migrations, barriers that prevent the access to the healthcare system must be removed, barriers that are accentuated by linguistic and cultural incomprehension, through adequate multidisciplinary healthcare settings such as the onetransdisciplinary we are presenting, composed of a medical doctor, an anthropologist and a cultural mediator.1